An Analysis of the Implementation of Good Governance Principles in the Management of Village-Owned Enterprises (BUMDes): A Case Study in Sabungan Village, Sipahutar District, North Tapanuli Regency - Elma Lastiarma; Susi Fitria Dewi; Al Rafni; Junaidi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the implementation of Good Governance principles in the management of the Village-Owned Enterprise (BUMDes) in Sabungan Village. The implementation of Good Governance is assessed through five sub-indicators: (1) Transparency, (2) Accountability, (3) Community Participation, (4) Efficiency and Effectiveness, and (5) Rule of Law.The research uses a Mixed Method approach with a Sequential Explanatory Design (quantitative followed by qualitative explanation). The study involved 92 respondents for the questionnaire and 13 informants selected through purposive sampling. Data collection techniques included questionnaires, interviews, and documentation. The validity of quantitative data was tested using validity and reliability tests, while qualitative data was validated using source triangulation. The quantitative findings indicate a high level of implementation of Good Governance principles in the management of BUMDes in Sabungan Village. The most strongly implemented principle was Accountability, with a percentage of 22.65% and 36.96% of respondents agreeing. In contrast, the lowest was Community Participation, with 18.05% and 28.70% agreement. The qualitative results revealed several challenges and strategies. The challenges include:(1) Limited capital in the management of BUMDes Martabe in Sabungan Village and its implications for business development,(2) Lack of public understanding of regulations in the use of BUMDes Martabe facilities, and(3) Non-compliance of some community members in repaying loans to BUMDes, reflecting low awareness levels. The proposed strategies to enhance the effectiveness and sustainability of locally-based BUMDes are:(1) Strengthening capital through deliberation and collective approaches,(2) Efforts to create transparent and equitable governance, and(3) Improving loan repayment compliance through the integration of local wisdom in BUMDes management, such as incorporating local values in various social and economic aspects. In this context, Batak social systems are emphasized, including:(1) Marsidapari (mutual cooperation in BUMDes management),(2) Marsipature Hutanabe (building the hometown together), and (3) Dalihan Na Tolu (a harmonious social structure).